Pemfaktoran Bilangan Prima pada Algoritme ElGamal untuk Keamanan Dokumen PDF - Aisyatul Karima; L. Budi Handoko; Ari Saputro (Departemen Teknik Elektro dan Teknologi Informasi, Fakultas Teknik, Universitas Gadjah Mada, 2017)
Utilization of document files does not guarantee the security of those documents. There are acts of plagiarism of txt and doc files. Converting files into PDF can help secure the files, because PDF can not be easily plagiarized and a password can be embedded into the files. But, nowadays, PDF files also can be modified by other parties, thus, reducing the security of the files. This paper utilizes factor of prime and random numbers in cryptography using ElGamal algorithm to encrypt PDF plaintext documents into cipher text. This research uses experimental research with some experiments of encryption and decryption. The data analysis type is quantitative with non-parametric statistic. This technique is implemented to analyze the final result of experiments. The research is conducted by doing 20 times encryption using random keys. The result shows the successfulness of encryption process. The process begins by converting each character from the plaintext using ASCII table to a decimal number. ElGamal algorithm calculation is then applied using prime and random numbers to generate the keys. This process makes ElGamal algorithm superior to other algorithm. The result is character value used in the decryption process. The output of the encryption process is an encrypted PDF document (ciphertext). The results show that the combinations of prime and random numbers are successfully generated in the encryption process using ElGamal algorithm.